Are echocardiographic parameters affected by body condition scores in blue-fronted Amazon parrots (Amazona aestiva, Linnaeus, 1758)? - dos Santos, Gisele Junqueira [UNESP]; Aleixo, Amanda Sarita Cruz [UNESP]; Hippólito, Alícia Giolo [UNESP]; Ferro, Barbara Sardela [UNESP]; Okamoto, Priscylla Tatiana Chalfun Guimarães [UNESP]; Lourenço, Maria Lucia Gomes [UNESP]; de Vasconcelos Machado, Vania Maria [UNESP]; Ramos, Paulo Roberto Rodrigues [UNESP]; Rahal, Sheila Canevese [UNESP]; Teixeira, Carlos Roberto [UNESP]; Melchert, Alessandra [UNESP] (Springer Nature, 2022)
This study aimed to determine the echocardiographic parameters of blue-fronted Amazon parrots (Amazona aestiva, Linnaeus, 1758) with varying body condition scores. Thirty-five birds only grown in captivity were included in the study and allocated into three different groups according to their respective body condition scores: Lean, Ideal, and Obese. The group of obese parrots presented lower right ventricle dimensions in diastole than lean parrots. The fractional shortening was considerably lower in obese parrots than in parrots with lean and ideal body condition scores but without statistical significance. The flow rate and the aortic pressure gradient were lower in the lean group than in the ideal group. The alterations in the nutritional state of captive blue-fronted amazon parrots may lead to cardiovascular dysfunctions detected through an echocardiographic evaluation, which represents an important diagnostic tool for these animals. The description of the techniques and the measures obtained in this study can contribute to future research in the area.
Keywords: Amazona aestiva; Cardiology; Echocardiography; Nutrition; Psittacidae